Mucosal injury following short term tracheal intubation: a novel animal model and composite injury score - Sinha, Rishie; Correia, Ricardo; Gardner, David; Grau-Roma, Llorenc; de Brot, Simone; Hardman, Jonathan; Morgan, Steve; Norris, Andrew (Wiley Open Access, 2018)
Objectives: Postintubation laryngotracheal injury is common. Assessment of histopathological changes currently requires animal models. We set about developing a viable, resource effective animal model to study these effects and to develop a detailed tissue injury score. Methods: Six pigs were anaesthetised using a standard regimen. We intubated the tracheas using a standard endotracheal tube modified to include optical sensors. Animals were anaesthetised for a duration of two to four hours, and their lungs were ventilated using a normoxic gas mixture. Following euthanasia, the tracheas were removed and underwent histological assessment by two independent veterinary pathologists. The histological lesions, including controls, were described and quantified, and two pathologists classified tissues according to a novel injury score. Results: Mean duration of tracheal intubation was 191 minutes (SD±41.6). In all except one animal, cuff pressures were maintained in the range of 25 – 45 cmH20. Histopathological findings in all study animals showed more extensive changes than previously described with short-term intubation. Changes were seen in all mucosal layers consistent with acute, suppurative and ulcerative tracheitis. The range of scores of the developed composite scoring system among the animals was wider than in earlier descriptions. There was a high percentage of agreement between both pathologists. Conclusions: We have described a novel tissue injury score to assess pathological changes following short term intubation in a viable animal model. The scoring system distinguished between the test animals as well as controls and may be appropriate for continuing study of intubation injury.